Improving the Practice of Financing Techniques and Technologies in the Field of Agriculture - Rinat Tauekelovich Sherbayev (Researchparks Publishing, 2022)
The article analyzes the processes of valuation of collateral, arising from the development and financing of projects implemented in agriculture in our country, approaches to evaluation, positive results expected by commercial banks that have financed projects through collateral, and types of collateral.